Effectiveness of higher order thinking skills (HOTS) based i-Think map concept towards primary students - Owi, Wei Ping; Ahmad, Azhar; Adnan, Mazlini; Hua, Ang Kean; Ang, Kean Hua (AIP Publishing, 2016)
Higher Order Thinking Skills (HOTS) is a new concept of education reform based on the Taxonomies Bloom. The concept concentrate on student understanding in learning process based on their own methods. Through the HOTS questions are able to train students to think creatively, critic and innovative. The aim of this study was to identify the student’s proficiency in solving HOTS Mathematics question by using i-Think map. This research takes place in Sabak Bernam, Selangor. The method applied is quantitative approach that involves approximately all of the standard five students. Pra-posttest was conduct before and after the intervention using i-Think map in solving the HOTS questions. The result indicates significant improvement for post-test, which prove that applying i-Think map enhance the students ability to solve HOTS question. Survey’s analysis showed 90% of the students agree having i-Thinking map in analysis the question carefully and using keywords in the map to solve the questions. As conclusion, this process benefits students to minimize in making the mistake when solving the questions. Therefore, teachers are necessarily to guide students in applying the eligible i-Think map and methods in analyzing the question through finding the keywords.